2014
DOI: 10.1073/pnas.1412616111
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-processing network in macaque visual cortex

Abstract: Our visual environment abounds with curved features. Thus, the goal of understanding visual processing should include the processing of curved features. Using functional magnetic resonance imaging in behaving monkeys, we demonstrated a network of cortical areas selective for the processing of curved features. This network includes three distinct hierarchically organized regions within the ventral visual pathway: a posterior curvature-biased patch (PCP) located in the near-foveal representation of dorsal V4, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 79 publications
13
99
1
Order By: Relevance
“…In subsequent analyses, we sought to constrain the functional interpretation of these responses. Are cortical regions in infants responding to highly specific visual categories124, to broader visual or semantic dimensions56, or to lower-level visual features that co-vary with high-level categories24252627? Do large-scale patterns of response to categories other than faces and scenes change over development?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In subsequent analyses, we sought to constrain the functional interpretation of these responses. Are cortical regions in infants responding to highly specific visual categories124, to broader visual or semantic dimensions56, or to lower-level visual features that co-vary with high-level categories24252627? Do large-scale patterns of response to categories other than faces and scenes change over development?…”
Section: Resultsmentioning
confidence: 99%
“…Do preferential responses to faces and scenes in infants reflect a high-level category preference, or a bias toward lower-level visual features, such as eccentricity, spatial frequency or rectilinearity (the presence of 90° angles)24252627? We tested whether cortical responses in infants were better predicted by these lower-level visual features than by high-level categories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of previous results in adolescents and adults, category-selective domains are correlated with a gradient of curvature/rectilinearity, with face-selective domains being correlated with preference for curvature729. We therefore chose to contrast monkey faces with rectilinear objects.…”
Section: Resultsmentioning
confidence: 99%
“…9, which show similar spatial organization for scrambled-face responsiveness and face selectivity. Further, it has been previously reported that even in adults face domains are also not absolutely face-selective, being broad enough to include other round objects and even curvy patterns72943. The shared selectivity for faces and scrambled faces cannot be explained by an initial semantically defined face template that is broadened, by experiencing the image statistics of faces, to include other round/curvy things; rather the broad selectivity itself must be innate.…”
Section: Discussionmentioning
confidence: 96%